2012
DOI: 10.3758/s13414-012-0405-x
|View full text |Cite
|
Sign up to set email alerts
|

How does horizontal and vertical navigation influence spatial memory of multifloored environments?

Abstract: Although a number of studies have been devoted to 2-D navigation, relatively little is known about how the brain encodes and recalls navigation in complex multifloored environments. Previous studies have proposed that humans preferentially memorize buildings by a set of horizontal 2-D representations. Yet this might stem from the fact that environments were also explored by floors. Here, we have investigated the effect of spatial learning on memory of a virtual multifloored building. Two groups of 28 participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 12 publications
2
48
2
Order By: Relevance
“…Several studies have reported that memory of vertically explored environments is poorer than that of horizontally explored environments (Hölscher, Meilinger, Vrachliotis, Brösamle, & Knauff, 2006;Jeffery, Jovalekic, Verriotis, & Hayman, 2013;Pasqualotto & Proulx, 2013;Thibault, Pasqualotto, Vidal, Droulez, & Berthoz, 2013). It is possible that a weaker spatial representation indicated, for example, by a poorer memory within the vertical dimension, results in poorer spatially-organised representation of numbers along the respective dimension.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that memory of vertically explored environments is poorer than that of horizontally explored environments (Hölscher, Meilinger, Vrachliotis, Brösamle, & Knauff, 2006;Jeffery, Jovalekic, Verriotis, & Hayman, 2013;Pasqualotto & Proulx, 2013;Thibault, Pasqualotto, Vidal, Droulez, & Berthoz, 2013). It is possible that a weaker spatial representation indicated, for example, by a poorer memory within the vertical dimension, results in poorer spatially-organised representation of numbers along the respective dimension.…”
Section: Discussionmentioning
confidence: 99%
“…Everyday life navigation mostly takes place in the horizontal plane. However, in some situations, such as finding the correct way in multi-floor buildings, humans also need to deal with an additional third dimension of space (3D) and to orient themselves correctly in the vertical plane (Thibault et al, 2013;Brandt et al, 2017). Previous studies in different animal species over the last decades revealed an anisotropy of performance and cellular activations in favor of the prevailing plane in groundbased species, such as dogs and rats, as well as flying species, such as bats and hummingbirds (Burt de Perera and Holbrook, 2012; Burt de Perera et al, 2013;Jeffery et al, 2013;Brandt and Dieterich, 2013;Flores-Abreu et al, 2014).…”
Section: D Navigation: Behavior Cerebral Network and Current Conceptsmentioning
confidence: 99%
“…; Thibault et al. ). In a number of instances, distinctive features can be used as landmarks to aid in these navigation processes.…”
Section: Introductionmentioning
confidence: 97%